Silicon Passivation by Ultrathin Hafnium Oxide Layer for Photoelectrochemical Applications - Staišiūnas, Laurynas; Kalinauskas, Putinas; Juzeliūnas, Eimutis; Grigucevičienė, Asta; Leinartas, Konstantinas; Niaura, Gediminas; Stanionytė, Sandra; Selskis, Algirdas (Frontiers in Chemistry, 2022)
Hafnium oxide (HfO2) films on silicon have the potential for application in photovoltaic devices. However, very little is known about the photoelectrochemical and protective properties of HfO2 films on Si. In this study, ultrathin films of HfO2 in the range of 15–70 nm were deposited on p-Si and Au substrates by atomic layer deposition (ALD). Grazing incidence X-ray diffraction (GI-XRD) identified the amorphous structure of the layers. Quartz crystal nanogravimetry (QCN) with Si and Au substrates indicated dynamics of electrolyte intake into the oxide film. No indications of oxide dissolution have been observed in acid (pH 3) and alkaline (pH 12) electrolytes. Mott–Schottky plots showed that the dark Si surface adjacent to the SiHfO2 interface is positively charged in an acid electrolyte and negatively charged in an alkaline electrolyte. The number of photoelectrons was determined to be much greater than the doping level of silicon. The cathodic photoactivity of the p-Si electrode protected by HfO2 films was studied with respect to the reaction of hydrogen reduction in acid and alkaline solutions. In acid solution, the film enhanced the reduction process when compared to that on the coating free electrode. The acceleration effect was explained in terms of prevention of silicon oxide formation, whose passivating capability is higher than that of hafnia films. In an alkaline electrolyte, an inhibition effect of the film was determined. Hafnia films protected Si from corrosion in this medium; however, at the same time, the film reduced electrode activity.